The Study of Humanistic Personality Psychology of the Main Character of the Novel Si Anak Pelangi by Tere Liye: The Value of Character Education and Its Relevance to Learning - Tri, Muhammad Agus (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
The purpose of this study is to examine the psychology of the humanistic personality of the main character of the novel Si Anak Pelangi Kakejiwaan of the main character of the novel Si Anak Pelangi by Tere Liye and the value of character education and its relevance to learning Indonesian in elementary school. The research method uses a descriptive qualitative approach based on the study of Habernas' humanistic psychology. The results of this study are Haberman's humanistic psychological theory, namely (1) technical learning, (2) practical learning, and (3) emancipatory learning. In addition, there are several values of character education such as, (1) hard work in the form of doing something diligently and accompanied by sincere intentions, (2) politeness in speech and behavior, (3) giving awards by sincerely accepting someone's gift, (4 ) positive, in acting both in sports and interacting with others, and (5) patient in dealing with insults and even insults from others to us.